2011
DOI: 10.1182/blood-2011-03-341404
|View full text |Cite
|
Sign up to set email alerts
|

Gene induction and repression during terminal erythropoiesis are mediated by distinct epigenetic changes

Abstract: It is unclear how epigenetic changes regulate the induction of erythroid-specific genes during terminal erythropoiesis. Here we use global mRNA sequencing (mRNA-seq) and chromatin immunoprecipitation coupled to high-throughput sequencing (CHIP-seq) to investigate the changes that occur in mRNA levels, RNA polymerase II (Pol II) occupancy, and multiple posttranslational histone modifications when erythroid progenitors differentiate into late erythroblasts. Among genes induced during this developmental transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 50 publications
10
129
1
1
Order By: Relevance
“…8), as has been seen for GATA1 ) and other TFs (Arvey et al 2012;Kundaje et al 2012). We have proposed that the permissive chromatin states are established no later than lineage commitment , based on the very limited changes observed in chromatin states during the substantial changes in gene expression during maturation after erythroid commitment (Wong et al 2011;Wu et al 2011). In our current study, we examined earlier stages of differentiation to infer some changes in chromatin states during lineage commitment.…”
Section: Discussionmentioning
confidence: 99%
“…8), as has been seen for GATA1 ) and other TFs (Arvey et al 2012;Kundaje et al 2012). We have proposed that the permissive chromatin states are established no later than lineage commitment , based on the very limited changes observed in chromatin states during the substantial changes in gene expression during maturation after erythroid commitment (Wong et al 2011;Wu et al 2011). In our current study, we examined earlier stages of differentiation to infer some changes in chromatin states during lineage commitment.…”
Section: Discussionmentioning
confidence: 99%
“…54 Changes in H4K16ac and H3K79me2 levels, rather than H3K4me3 and H3K27me3, are most predictive of the direction in changes in gene expression during terminal fetal liver erythroid differentiation. 55 Because H3K4me3 is usually associated with transcriptional initiation whereas H3K79me2 is tightly correlated with transcription elongation, control of Pol II elongation could be a mechanism for regulating erythroid gene expression. This may be mediated by GATA1 or TAL1 or their associated complexes, especially because nearby regions of genes induced during terminal erythroid development are co-occupied by these factors.…”
Section: Epigenetic Changes In Chromatin During Erythroid Differentiamentioning
confidence: 99%
“…In support of this view, a recent genome-wide histone modification profiling study, performed in differentiating erythroid cells, suggested that the regulation of transcription elongation plays a key role in gene induction and repression processes during cellular differentiation. 37 Future investigations will reveal whether direct transcription elongation stimulation by enhancers is a general mechanism.…”
Section: Acknowledgmentsmentioning
confidence: 99%